Peran Guru Bimbingan dan Konseling (BK) untuk Meningkatkan Resiliensi Siswa dengan Orang Tua Bercerai di Kabupaten Jember - Sheilla Kusuma Wardhani; Erdi Istiaji; Novia Luthviatin (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2026)
Parental divorce significantly impacts adolescents’ mental health, such as causing stress, depression, and reduced adaptive abilities. This study aims to analyze the role of Guidance and Counseling teachers in strengthening the resilience of students with divorced parents in Jember Regency, using the Stimulus-Organism-Response (S-O-R) theory. This research is a qualitative study with a phenomenological approach. Informants were selected using purposive sampling, consisting of seven BK teachers as primary informants and three students as additional informants. Data were collected through in-depth interviews and analyzed using thematic analysis. The research findings indicate that most Guidance and Counseling teachers assess and identify the resilience of students from divorced families using unstructured and unsystematic methods, such as spontaneous interviews during counseling sessions and daily behavior observations. Education about resilience is also delivered informally, often through spontaneous advice during individual counseling. BK teachers actively help students address negative thought patterns and develop coping skills, primarily using an emotion-focused coping approach. Collaboration with parents, teachers, peers, and psychologists is carried out by most BK teachers, although one teacher refrains from collaboration due to a student's confidentiality request. Measurable and continuous evaluation instruments are not widely used; instead, teachers rely on informal approaches such as regular consultations, social observation, and cooperation with homeroom teachers and close peers.